Men with a history of commercial heterosexual contact play essential roles in the transmission of HIV-1 CRF55_01B from men who have sex with men to the general population in Guangxi, China - Luo, Tong; Zhang, Fei; Liang, Huayue; Yu, Dee; Cen, Ping; Zhong, Shanmei; Qin, Cai; Yang, Yuan; Jiang, Jiaxiao; Liao, Yanyan; Li, Mu; Zhang, Rongjing; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundThere is increasing focus on HIV-1 CRF55_01B in China. However, there is limited information regarding the dissemination of CRF55_01B across different regions and populations in Guangxi. This study was performed to elucidate the evolutionary history of the introduction and dissemination of CRF55_01B in Guangxi.MethodsMolecular network and phylogenetic analyses were used to investigate the transmission characteristics of CRF55_01B in China. The analyses particularly focused on the cross-provincial spatial and temporal transmission patterns between Guangdong Province and Guangxi, as well as the transmission dynamics among different regions and populations within Guangxi.ResultsIn total, 2226 partial pol sequences of CRF55_01B strains sampled from 2007 to 2022 were collected, including 1895 (85.09%) sequences from Guangdong, 199 (8.94%) sequences from Guangxi, and 172 (7.59%) sequences from other provinces of China. Most people living with HIV in Guangxi were infected with HIV-1 through heterosexuals (52.76%). Among these, 19.10% had a history of commercial heterosexual contact (CHC) and 15.58% had a history of non-marital non-commercial heterosexual contact (NMNCHC). Overall, 1418 sequences were identified in the molecular network. Notably, the sequences from Guangdong Province were most closely linked to those from Guangxi. Phylogenetic analysis showed that CRF55_01B was first introduced from Shenzhen City to Nanning City around 2007. Subsequently, CRF55_01B established local transmission within Guangxi, with Nanning City serving as the transmission center from 2008 to 2017. After 2017, the CRF55_01B strain spread to other regions of Guangxi. Men who have sex with men (MSM) and men with a history of CHC have played a significant role in the transmission of CRF55_01B among different populations in Guangxi.ConclusionsThis study provides evidence on the transmission trajectory of CRF55_01B among different regions and populations in Guangxi. Given the bridging role of men with a history of CHC in the dissemination of CRF55_01B from MSM to the general population, it is imperative to enhance surveillance among key populations to mitigate the secondary transmission of HIV-1.